Unmasking Nigeria"s leadership conundrum: The role of the church - Onuorah, Chioma P. (HTS teologiese studies, 2024)
The intricacies of Nigeria’s leadership challenges present a formidable obstacle to the nation’s progress. Corruption, political instability, and ethnic and religious tensions form a complex web that impedes development. While studies often analyse the political mobilisation of religious groups, some failed to recognise their potential to bring about positive changes in governance. This research addresses this gap by examining how the Church, with its network and moral influence, can tackle Nigeria’s leadership hurdles and promote sustainable development. Utilising historical and descriptive research methods, the study explores the Church’s involvement in shaping Nigerian society and politics. It acknowledges the challenges the Church faces in navigating the socio-political landscape and highlights its role in advocating for ethical leadership and effective governance. By exploring both historical contexts and contemporary realities, the article emphasises the importance of the Church’s active engagement in advancing Nigeria’s democratic progress and socio-economic growth, offering valuable insights for civil society and religious organisations to enhance their collaboration.Contribution: This study significantly contributes to tackling leadership challenges in Nigeria by emphasising the crucial role of the Church and promoting collaborative governance approaches as a means to achieve positive societal change and transformation.